Clean extracts from accumulator efficiently improved Solanum nigrum L. accumulating Cd and Pb in soil. (1st December 2019) - Han, Ran; Dai, Huiping; Zhan, Jie; Wei, Shuhe
Abstract: To find more clean and efficient chelator promoted hyperaccumulation of heavy metal from contaminated soil is a challenge in phytoremediation. The aim of this experiment was to explore the roles of aqueous extracts from the roots, stems and leaves of three accumulators on Solanum nigrum L. accumulating Cd and Pb from soil in comparation with the chelator Ethylenediaminetetraacetic acid (EDTA). The results of soil pot culture experiment showed that Cd and Pb concentrations of S. nigrum shoot significantly increased by 62.1% and 39.8% when the stem extracts of Bidens tripartita L. (BTS) was spiked to soil, which were higher (p < 0.05) than that of spiked EDTA (35.7%, 26.3%). The biomasses of S. nigrum significantly decreased (p < 0.05) by the EDTA addition, but were not impacted when BTS added. Accordingly, the extractable Cd and Pb concentrations in soils of S. nigrum rhizospheres and in leaching experiment were significantly higher (p < 0.05) in the BTS treatments than EDTA. There were not significant effects of these extracts on soil pH. The concentrations of soluble polysaccharide, total organic acid and reducing sugar in BTS were much higher than that of other extracts, which might be part reasons of it strongly promoted S. nigrum accumulating Cd and Pb from soil. Furthermore, the bacterial count and some enzyme activities in soils treated with BTS were higher than that of EDTA either. Basically, BTS was more efficient in S. nigrum accumulating Cd and Pb in soils than that of EDTA, and did not have side effects on plant growth and soil environment, i.e. more clean either in this sense. This new substitutable chelator for EDTA was of great significance for phytoremediation and cleaner production. Graphical abstract: Image 106783